2013
DOI: 10.1111/apa.12152
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and behaviour of boys and parents about circumcision

Abstract: We consider that it is reasonable to wait up to an age at which the child could understand and participate in the decision of the concept and timing of circumcision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Traditional circumcisers are still preferred by parents (3,22). In Corduk et al's study, it was found out that 42% of boys were operated on by a circumciser (23). Our results indicate that the traditional approach is still common in Turkey.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Traditional circumcisers are still preferred by parents (3,22). In Corduk et al's study, it was found out that 42% of boys were operated on by a circumciser (23). Our results indicate that the traditional approach is still common in Turkey.…”
Section: Discussionmentioning
confidence: 55%
“…Knowledge that other children are being circumcised by force and without an explanation of what's going to happen, without being prepared and anesthetized will increase fear and psychic trauma. In Corduk et al's study, 38% of boys stated that they were frightened during circumcision (23). In their study, Verit et al stated that of males between 25 and 45 years of age, 81% stated that they were circumcised by traditional circumcisers rather than surgeons and 90% were found to have been circumcised at home (22).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The fact that our participants were children over the phallic period may account for such an inconsistency. Supporting this assumption, Corduk et al 20 reported that worry and fear levels of children over 7 years of age were lower than those under age 7. In addition, cultural factors may also play a role in the mentioned differences in the results.…”
Section: Discussionmentioning
confidence: 94%
“…Based on psychoanalytic theory, male children are vulnerable to castration anxiety, especially within the phallic period, -which includes 3 to 6 ages-meaning they are likely to be scared of experiencing penile injury. 19 Likewise, Corduk et al 20 investigated the fear and worry about the circumcision retrospectively in children and reported that nearly half of the children felt worry and one third had feared from circumcision operation. However, our findings were inconsistent with those obtained in previous studies.…”
Section: Discussionmentioning
confidence: 99%